Aspects of the ecology of the shrimp Palaemon pacificus (Stimpson) (Decapoda,Palaemonidae) in the Bushmans river estuary - Robertson, Wendy Daryl (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1984)
The recruitment of Palaemon pacificus to the Bushmans River estuary was studied over a 12 month period. The dynamics of a population of shrimps in a small, tidal channel in the lower reaches of the estuary was investigated over a similar time span. Temperature and salinity tolerances of various stages and sizes of shrimps were compared in controlled experiments and are discussed in the light of the distribution and general ecology of the shrimp. Stage 6 zoeae and post-larvae entered the estuary on nocturnal flood tides throughout the year with peak recruitment occurring in March/April. The population of shrimps in the study site was predominantly juvenile for most of the year, with peak sub-adult numbers occurring in midsummer. The sex ratio was female-biased throughout the year except for short bursts of male predominance in February and April. Average growth rate was 0,043 mm carapace length per day. Maximum residence time in the study site was estimated to be four months and in the estuary at least six months. Flooding of the estuary resulted in a considerable reduction in juvenile numbers in the study site and some loss of sub-adults. Shrimps tolerated a temperature range of 4,3 to 30,9â °C for 144 hours. Their long term tolerance range is probably narrower (10 to 28â °C) because of the effects of temperature related factors such as starvation and disease. Their distribution in South Africa (Olifants River to Kosi Bay ) is consistent with this tolerance range. Sub-adults tolerated salinities of 1 to 79 "° and post-larvae 2 to 60 "° at 15â °C for 144 hours. Low moulting success (low and high salinities ) and starvation (high salinities) would probably reduce these tolerance ranges to 2 to 56 "° (sub-adults) and 4 to 56 "° (post-larvae). Higher and lower temperatures (10 and 20â °C) reduced the tolerance of post-larvae to low salinities, but sub-adults were only affected at 30â °C. Stages 4 and 5 and stage 6 zoeae were intolerant of salinities below 14 "°. The development of salinity tolerance with age is consistent with the retention of a marine breeding phase. It also explains the high loss of juveniles from the study site following the flood. It is postulated that recovery of the population after a flood would be fairly rapid except in extreme cases when estuarine vegetation is severely affected.
Keywords: Shrimps -- South Africa